Literature Review of the Effect of Parenting on the Learning of Dyslexic Learners in Inclusive Schools Between 2019-2024 - Qomariah, Oom; Rokhman, Fathur; Pramono, Suwito Eko; Subali, Bambang; Widiarti, Nuni (research, training and philanthropy institution Natural Aceh, 2025)
This article was written to present a literature review to find out the forms of parenting that affect the learning of dyslexic students in Inclusive Schools in the period between 2019 and 2024. The method used in this research is a Systematic Literature Review (SLR). Data was obtained from journal articles, research reports, and proceedings aligned with the paper's topic using the help of Harzing's Publish or Perish. Parenting has a vital role in shaping the behavior, social skills, and academic achievement of dyslexic learners. From the search for articles on parenting patterns of dyslexic learners in the 2019-2024 time span, there were 16 articles consisting of 11 journal articles, four research reports, and one proceeding. The results showed that democratic and supportive parenting consistently improved the engagement and learning outcomes, independence, and self-confidence of dyslexic children. Meanwhile, authoritarian and permissive parenting showed mixed impacts, often impeding educational progress. In addition, this study highlights the importance of collaboration between parents, educators, and support personnel in creating an inclusive and adaptive learning environment. The implications of this study suggest that ongoing support from families and educational environments is essential to achieve optimal learning outcomes for dyslexic learners.